(untitled) (Philosophy and Progress, 2025)
Scholars argue that if the planet is to be habitable, there is no other option except to slow the phenomenal pace of climate change. Meaningful climate mitigation actions are the best way to control it. Due to global pressure, lawmakers took numerous mitigation measures to limit the world average temperatures below 2°C over pre-industrial levels and still try to restrict the increase to 1.5°C. However, the steps failed to materialize their aspirations. This failure is frequently blamed on world leaders’ paradoxical stances. Considering this backdrop, the study aims to investigate global leaders’ paradoxes in climate mitigation actions. This qualitative study employed content analysis methods to achieve its goal by using United Nations Framework Convention on Climate Change and United Nations Environment Programme as primary sources and Intergovernmental Panel on Climate Change Reports, books, journal articles, and dissertations as secondary sources. This study reveals that global leaders prioritizing their economy, geopolitics, fossil fuel consumption, and business interests that encouraged them to behave paradoxically. This study recommends that world leaders should set aside conflicts of interest, prioritize climate justice and overcome the climate policy commitment-action gap. Otherwise, an authoritarian form of climate change will affect everyone regardless of economic or geographic status. Philosophy and Progress, Vol#75-76; No#1-2; Jan-Dec 2024 P 227-252